Application of WordNet and word embeddings in the development of prototypes for automatic language generation (Linguamática, 2020)
This presentation of two prototypes of automatic natural language generation provides an overview of the methodology applied in the description and processing of linguistic data, as well as of the techniques and tools already existing or developed in order to guarantee the functioning of the simulators in German, Spanish and French.
Keywords: Valency Grammar; Argument patterns; Natural Language Processing; Natural Language Generation; WordNet; word embeddings